P-98 Lessons learnt from an audit of corneal donation in St Clare Hospice in-patient unit. (19th November 2022) - Abbas, Syed Qamar; Kingdon, Arjun; Saxena, Helen
Abstract : Introduction: 80% of people in England support organ donation but few are aware of the option of donating their corneas, which far more dying people are eligible to do than is widely recognised. Through proactively initiating conversations, hospices have the opportunity to contribute to reducing the national shortfall considerably. Methods: Standard audit methodology of forty consecutive electronic (SystmOne) patient records from June to September 2021, including searches of read codes and textual searches. Analysis and results: 70% of admitted patients were eligible to donate their corneas. Of these, discussions were held with those patients and it resulted in willingness about donation of corneas in four cases (14%). In all four cases, the patient was willing to proceed with corneal donation and in the case of three of these patients who died on the in-patient unit, corneal donation was able to proceed. The number of documented conversations increased when a key experienced member of staff re-joined the medical team following extended leave. Conclusion: Work remains to be done to encourage routine discussion of corneal donation on the in-patient unit. When discussed, the discussions seem to be well received and have positive outcomes. Multiple interventions have subsequently been undertaken, including whole-hospice education sessions, a themed journal club discussion, and update of junior doctor induction material. With high turnover of rotating junior doctors, presence of experienced IPU doctors is key to ensuring that a culture of routine corneal donation discussion is embedded in the unit. There is potential for nursing staff to play a larger role in these conversations.